Implementation Of Partnership Between Midwives And Traditional Healers In Childbirth Assistance At Puskesmas Munjul Pandeglang District - Eka Maryanti; Harimat Hendarwan (Jurnal EduHealth, 2025)
One of the efforts of the Pandeglang Regency Government to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) is by...Pandeglang Regent Regulation Number 19 of 2021 concerning the Acceleration of the Reduction of Maternal and Infant Mortality, one way to increase the coverage of deliveries and prevent maternal and infant mortality isinitiated a partnership program between Village Midwives and Paraji after the issuance of the Regent's Regulation. Maternal and infant deaths still occur in Pandeglang Regency.In 2023, the infant mortality rate was 196 cases and 30 maternal deaths. The method used was Descriptive Qualitative with data collection using Observation, Interview and Documentation techniques. Using the implementation theory of Edward III (Communication, Resources, Disposition and Bureaucracy). The informants consist of Main Informants (Midwives and Paraji shamans) and supporting informants (PJ Kia Dinkes, PJ Kia Puskesmas and Head of Puskesmas). Research Results Implementation of Pandeglang district government policies in Perbup No. 19 of 2021 in order to accelerate the reduction in maternal and infant mortality rates, namely the partnership program between midwives and paraji shamans in assisting childbirth has been implemented in accordance with Edward III's Theory.